Deformation behaviour and strength of frozen sand - Parameswaran, V. R. (1980)
Uniaxial unconfined compression tests were carried out on frozen saturated Ottawa sand containing about 20% by weight of water, at temperatures between -2 and -15 degrees C, and at strain rates varying between 10[-7] and 10[-2]s[-1]. The compressive strength and the initial tangent modulus increased with increasing strain rate and with decreasing temperature. At -2 degrees C, values of strength and modulus were considerably lower than those predicted by linear extrapolation of the values observed at lower temperatures, on a log-log scale. This could be due to the presence of unfrozen water in the samples at -2 degrees C. Des essais de compression simple ont été faits sur du sable d'Ottawa gelé, saturé à une teneur en eau de 20%, sous des températures de -2 à -15 degrés C, et à des vitesses de déformation variant de 10[-7] à 10[-2]s[-1]. La résistance en compression et le module tangent initial augmente avec une augmentation de la vitesse de déformation et une diminution de la température. A -2 degrés C, les valeurs de la résistance et du module sont considérablement plus faibles que celles déduites d'une extrapolation linéaire sur une échelle log-log des résultats obtenus à plus basse température. Ceci peut être dû à la présence d'eau non gelée dans les échantillons à -2 degrés C. Peer reviewed: Yes NRC publication: Yes